When socio-technical imaginaries meet the reality of adoption: Cobots in manufacturing - Hearn, Greg; Channa, Nisar Ahmed; Casali, Gian Luca (Futures : the journal of policy, planning and futures studies, 2025)
By the time a new technology is adopted, it has been significantly influenced by the socio-technical imaginaries that inspired its development. For Cobots, the juxtaposition of the imaginaries with the realities for workforces is starkest at the point of adoption. However, as the diffusion of Cobots is relatively new, there is a lack of empirical research on how Cobots will affect the future workforce and the potential implications of Cobots for industries. Given this, we adopted the Gioia methodological approach to conduct a qualitative content analysis of online news articles, blogs, viewpoints, vlogs, and interviews with pioneers in Cobotics technology published on different websites. This resulted in four themes: Cobot diffusion and Commercial Rationales; Applications of Cobots Across the Industries; Cobots and Future Employment Landscape; and Implications for Manufacturing Work. We then developed high level composite socio-technical narratives implied in the corpus vis Efficiency, Skills, Safety, Wellbeing, Resilience, Change Management. By comparing these narratives with extant empirical studies of Cobot adoption in manufacturing, we conclude that the current dominant sociotechnical narrative for Cobot adoption in manufacturing is simple automation. It is efficiency driven at the level of firm, and substitutive rather than collaborative at the level of work task. •We discuss how socio-technical imaginaries inform or are challenged by the Cobot adoption process in manufacturing.•We compare public commentary and empirical research on Cobots’ impact on traditional ways in which workers do their jobs.•We present important socio-technical narratives from public commentary namely: Efficiency, Skills, Safety, Wellbeing, Resilience, Change Management.•Empirical studies of actual Cobot adoption in manufacturing, suggest the dominant sociotechnical narrative for Cobot adoption in manufacturing is simple automation.